2011
DOI: 10.1590/s1413-70542011000100005
|View full text |Cite
|
Sign up to set email alerts
|

Couve-flor cultivada em substrato: marcha de absorção de macronutrientes e micronutrientes

Abstract: RESUMOCom o objetivo de avaliar marcha de absorção de macro e micronutrientes na couve-flor cultivada em substrato, um experimento foi conduzido em casa de vegetação da UNESP, Campus de Jaboticabal, SP. O delineamento experimental foi de blocos ao acaso, com seis tratamentos e cinco repetições. Os tratamentos foram constituídos pelas épocas de amostragem (20; 30; 40; 50; 60 e 70 dias após o transplante). Avaliaram-se os teores e acúmulo dos macro e micronutrientes da parte aérea e raiz. A maior demanda de nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 2 publications
(1 reference statement)
2
7
0
2
Order By: Relevance
“…Regarding micronutrient accumulation, the total Fe accumulated was of 19.69 mg plant -1 at 75 DAT, making it the most required micronutrient by the culture, as also observed by Castoldi et al (2009) and Alves et al (2011) in cauliflower culture.…”
Section: Micronutrient Accumulationsupporting
confidence: 55%
See 2 more Smart Citations
“…Regarding micronutrient accumulation, the total Fe accumulated was of 19.69 mg plant -1 at 75 DAT, making it the most required micronutrient by the culture, as also observed by Castoldi et al (2009) and Alves et al (2011) in cauliflower culture.…”
Section: Micronutrient Accumulationsupporting
confidence: 55%
“…Similar to what was found for Fe and macronutrients, the period of highest Mn accumulation occurred during the highest broccoli dry matter accumulation period (35-55 DAT). However, during inflorescence formation (55 to 75 DAT), it was observed that Mn, unlike other nutrients, was continuously demanded until the end of cycle, similarly to the result by Alves et al (2011).…”
Section: Micronutrient Accumulationmentioning
confidence: 63%
See 1 more Smart Citation
“…A ordem de acúmulo dos nutrientes foi K > N > Ca > S > Mg >P, mostrando a importância tanto do K como do N na composição das mudas, com valores muito superiores aos demais nutrientes. Também, em couve-flor e repolho, pertencentes à mesma espécie do brócolis, o N e o K foram os nutrientes mais acumulados na planta (Alves et al, 2011;Corrêa et al, 2013).…”
Section: Resultados E Discussão Características Das Mudas Antes Do Trunclassified
“…Além do manejo d'água, a nutrição é outro importante componente para a produção da couve-flor e exerce grande influência na produtividade e na qualidade da inflorescência imatura, sendo o boro um dos principais fatores limitante (Alves et al, 2011;Cecílio Filho et al, 2015).…”
Section: Introductionunclassified